PERAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI DALAM MENINGKATKAN KINERJA GURU SMP DI KABUPATEN TEMANGGUNG - Barorotul Aifa'iyah; Sungkowo Edy Mulyono; Sugi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Teacher performance is a crucial determinant of educational quality; however, empirical evidence indicates that the performance of junior high school teachers, particularly English teachers in Temanggung Regency, has not yet reached an optimal level. This study aims to analyze the effects of work motivation, principal leadership, and emotional intelligence on teacher performance, as well as to examine the moderating role of organizational culture. The study employed a quantitative exploratory design. The population consisted of 149 public and private junior high school English teachers who are members of the Subject Teacher Working Group (MGMP) in Temanggung Regency. Using the Slovin formula, 109 teachers were selected through random sampling. Data were collected using a closed-ended questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The analysis included descriptive statistics and outer model testing, covering convergent validity, discriminant validity, and construct reliability, all of which met criteria. Inner model testing assessed model fit, multicollinearity, and effect size, indicating that the model was fit and free from problems. The results show that work motivation, principal leadership, and emotional intelligence have a positive and significant effect on teacher performance. Furthermore, organizational culture significantly moderates the relationship between these independent variables and teacher performance, thereby strengthening their influence. In conclusion, improving teacher performance is not solely determined by individual attributes and leadership quality, but is also influenced by the strength of school organizational culture. Therefore, fostering a collaborative and supportive organizational culture is an essential strategy for enhancing teacher performance in schools.